EFFECTIVENESS OF EFFLEURAGE MASSAGE AND LAVENDER AROMATHERAPY ON ADOLESCENTS WITH ACUTE PRIMARY DYSMENORRHEA PAIN IN PRIGI VILLAGE, PADAMARA DISTRICT - Shara Dhianing; Gusti, Mariah Ulfah (PT. Radja Intercontinental Publishing, 2024)
Background: Dysmenorrhea during menstruation is a condition where the pain in the abdomen starts from the lower abdomen which sometimes the pain can extend to the back, lower back and thighs that can carry out routine activities as usual and not a few can interfere with daily activities . Pain in dysmenorrhea can be treated with various alternatives, both pharmacologically and non-pharmacologically. Pharmacologically, it can be treated with analgesic drugs. One natural method that is considered effective in reducing menstrual pain is effleurage massage and lavender aromatherapy. Objective: This case study aims to describe the application of effleurage massage and lavender aromatherapy in adolescents with acute pain dysmenorrhea in Prigi Village, Padamara District. Methods: Case study conducted by observation for 3x meetings and intervention of giving Massage Effleurage and lavender aromatherapy for 3 days on November 6-8, 2024. Results: The results of the case study of the application of giving effleurage massage and lavender aromatherapy on the first day the patient was still in pain by showing a decrease in the pain scale on the second and third days. On the first day, the pain level was on scale 6 (severe pain), on the second day the pain level decreased to scale 4 (moderate pain) and on the third day the pain scale dropped to scale 3 (mild pain). Conclusion: Massage Effleurage and lavender aromatherapy in adolescents with dysminorrhea in Prigi Village are effective in reducing pain applied for 3x24 hours showing significant results from a pain scale of 6 (severe pain) to a pain scale of 3 (mild pain).